Perencanaan Dan Pembuatan Aplikasi Rumah Makan X Berbasis Android - Ronny Limowa; Kristo Radion Purba; Lily Puspa Dewi (Jurnal Infra, 2018)
The development of information technology on this day has reached the point where everyone can connect to each other easily, quickly and efficiently. Of the many devices resulting from the advancement of information technology, Smartphone is a communication tool that serves to receive and transmit the most widely used information due to its nature that is easy to carry anywhere.So far, the ongoing ordering system is still conventional. The current food and beverage ordering system at Restaurant X is still manual and not computerized.This android application based Restaurant X is created as an alternative to replace the ordering system that is currently running on Restaurant X. This program uses MySQL as a local database storage container and also uses Android Studio as a programming language application to create an X Restaurant app. Expected with this application the customer can more easily in ordering and Restaurant X can also be helped.